The religious self‐alteration of Shem Irofa'alu during the anti‐colonial Maasina Rule in Solomon Islands (1944–1953). Issue 1 (10th March 2023) - Timmer, Jaap; Frazer, Ian
Abstract: This essay explores the post‐World War Two anti‐colonial Maasina Rule in north Malaita, Solomon Islands, to show how a church leader Shem Irofa'alu decided to establish a religious movement independent of the state and the traditional evangelical church. Irofa'alu's movement indexes an important moment of culture change towards increasing enthusiasm for the often‐overlooked Christianity‐based forms of sovereignty in the region. It highlights that Maasina Rule was not only a powerful rupture in social processes, but also sharpened the growing division between state and church. Irofa'alu's role in Maasina Rule shows that his influence peaked between 1948 and 1950 and then went into rapid decline. This change in fortune coincided with a critical turning point in the colonial government's attempts to end the movement through appeasement. No longer the head of the evangelical church in Malu'u sub‐district and frustrated about the mother church's governance, Irofa'alu retreated to his home area and set about establishing a new church, Boboa ('Foundation'), his first attempt at organizing a self‐governing assembly before introducing Jehovah's Witnesses in north Malaita. In later years, Irofa'alu became a prophet‐exemplar for new generations of religious leaders trying to establish Malaitan sovereignties based on their own power to move the truth of prophecies away from foreign state and church organizations.